Greenhouse Gas Emissions from Flood-Irrigated Rice as Affected by Phosphorus Fertilizer Source - Chandler M. Arel; Kristofor R. Brye; Diego Della Lunga; Trenton L. Roberts; Richard Adams (Agriculture)
Research into alternative phosphorus (P) fertilizer sources that may be able to supplement P resources is necessary. Struvite (MgNH4PO4 · 6H2O) can be made by removing excess nutrients from waste sources and may reduce greenhouse gas (GHG) emissions from cropping systems. This study sought to quantify GHG [i.e., methane (CH4), nitrous oxide (N2O), and carbon dioxide (CO2)] fluxes, season-long emissions, and net GHG emissions from chemically precipitated struvite (CPST) and synthetic and real-wastewater-derived electrochemically precipitated struvite (ECST) compared to monoammonium phosphate (MAP) and an unamended control (UC) from flood-irrigated rice (Oryza sativa) grown in P-deficient, silt loam soil in a greenhouse. Gas samples were collected weekly over a 140-day period in 2022. Methane and CO2 emissions differed (p < 0.05) among P fertilizer sources, while N2O emissions were similar among all treatments. Methane, CO2, and N2O emissions from MAP-fertilized rice were the greatest (98.7, 20,960, and 0.44 kg ha−1 season−1, respectively), but they were similar to those of CH4 and CO2 for CPST and those of N2O for all other P fertilizer sources. Season-long CH4, CO2, and N2O emissions and net GHG emissions did not differ between ECST materials. This study’s results emphasized the potential that wastewater-recovered struvite has to reduce GHG emissions in rice production systems.